Reformasi Pendidikan Islam Masyarakat Daerah Terluar di Indonesia - Khairul, Agus; Sugiri, R. Asep Hidayat (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
This research aims to find out how to reform Indonesia's Islamic Education in the face of Islamic Education of the outermost regional communities. The results of the library study state that the reform of Indonesian Islamic Education in the face of Islamic Education of the outermost local community is by expanding access and improving the quality of Islamic Education in several ways. First, the increase in the capacity of Islamic Education institutions. Second, the improvement of the equalization of Islamic Education through the increasing effectiveness of the affirmative policy, as well as the provision of special scholarships for the poor and the implementation of quality distance education. Third, the provision of operational costs to improve the effectiveness of education. The policy carried out by the Ministry of Education and Culture to accelerate development in the 3T area is an advanced program together to educate Indonesia. This program includes The Integrated Teacher Professional Education Program With Additional Authority (PPGT), Undergraduate Program of Educating in 3T (SM3T) area, Frontline Teacher (GGD), Regional Development Program, and Collaborative Integrated Teacher Professional Education (PPGT collaborative).